High reactivity of deep biota under anthropogenic CO2 injection into basalt. Issue 1 (December 2017) - Trias, Rosalia; Ménez, Bénédicte; Campion, Paul; Zivanovic, Yvan; Lecourt, Léna; Lecoeuvre, Aurélien; Schmitt-Kopplin, Philippe; Uhl, Jenny; Gislason, Sigurður; Alfreðsson, Helgi; Mesfin, Kiflom; Snæbjörnsdóttir, Sandra; et al.
Abstract Basalts are recognized as one of the major habitats on Earth, harboring diverse and active microbial populations. Inconsistently, this living component is rarely considered in engineering operations carried out in these environments. This includes carbon capture and storage (CCS) technologies that seek to offset anthropogenic CO2 emissions into the atmosphere by burying this greenhouse gas in the subsurface. Here, we show that deep ecosystems respond quickly to field operations associated with CO2 injections based on a microbiological survey of a basaltic CCS site. Acidic CO2 -charged groundwater results in a marked decrease (by ~ 2.5–4) in microbial richness despite observable blooms of lithoautotrophic iron-oxidizing Betaproteobacteria and degraders of aromatic compounds, which hence impact the aquifer redox state and the carbon fate. Host-basalt dissolution releases nutrients and energy sources, which sustain the growth of autotrophic and heterotrophic species whose activities may have consequences on mineral storage. The impacts of carbon capture and storage (CCS) on subsurface microorganisms are poorly understood. Here, the authors show that deep ecosystems respond quickly to CO2 injections and that the environmental consequences of their metabolic activities need to be properly assessed for sustainable CCS in basalt.